The Influence of Leadership Style on Management Systems in Hospitals: Literature Review - Sembiring, Nur Maghribi; Sembiring, Muhammad Simba (Journal of Bionursing, 2025)
Background : Leadership style is a norm of the actor used by a person when the person tries to influence the behavior of others. Leadership style is appropriate if the company's goals have been communicated and subordinates have accepted them. A leader must apply a leadership style to manage his subordinates, because a leader will greatly influence the success of the organization in achieving its goals. The hospital is an integral part of a social and health organization with the function of providing comprehensive services, curative and preventive services to the community. Human resource management is the most important element in achieving organizational goals. Aim : to formulate how a leader influences his leadership style by paying attention to the management system in the hospital. The data used in this study are secondary data obtained from the results of research conducted by previous researchers. Data sources are in the form of articles or journals that are relevant to this topic. Method : The articles obtained amounted to 13 articles from 2021 - 2024. The data search was carried out using the Google Scholar database with the keywords "Leadership Against Management Systems" and Proquest with the keywords "Leadership and Management", ScienceDirect with the keywords "Leadership Style or Management System". Result : There is an influence of a leader in implementing his leadership style by paying attention to the management system in the hospital. Conclusion : All of this is related to the Performance of All Hospital Employees (Medical Personnel and Staff), the Performance of Medical Personnel on the Quality of Service in the Hospital, the Work Spirit of Hospital Employees, the Innovative Work Behavior of Hospital Employees, Leadership Style in Private Hospitals and State Hospitals.